TH-PAM multiple access scheme for 60 GHz pulse wireless communication system - Yongbin ZHANG; Xuehua LI; Boxu YAO (Dianxin kexue)
In view of the multi-user interference problem in 60 GHz pulse wireless communication system，the performance of the system based on TH-PAM multiple modulation scheme was studied. Under the IEEE 802.15.3.c channel model，relationship analysis model between system BER performance，communication distance and number of user was put forward，multi-user interference characteristics of the system with TH-PAM multiple access modulation was studied. It was compared with TH-PPM multiple access system. Simulation results show that the BER of TH-PAM multiple access system can keep below 10-5 within the scope of the communication distance is less than 30 meters，and the BER of TH-PPM multiple access system is always greater than 10-4 in range of 100 meters. As a result，TH-PAM was more suitable for 60 GHz short-range wireless communication than TH-PPM and provided technical reference for hot high capacity scenario of 5G high-frequency new hollow.